ANALISIS HASIL BELAJAR MATEMATIKA SISWA KELAS VIII PADA MATERI BANGUN RUANG SISI DATAR - Larosa, Muspardin; Mendrofa, Netti Kariani (Academy of Education Journal, 2023)
Student learning outcomes are a reference for educators to determine the success or failure of students in carrying out the learning process in class. This study aims to determine the factors that influence mathematics learning outcomes in the material of flat-sided geometric shapes at SMP Negeri 4 Gunungsitoli Idanoi. The subjects of this study were class VIII students with 26 students. The instruments used in the study were a test of 5 questions and interviews. The data analysis method used in this study is a quantitative descriptive method. Based on the data exposure, the researchers concluded that the average student learning achievement was 73.00. From the data on student learning outcomes test scores above, a standard deviation of 11.1 was obtained from 26 respondents. Students with moderate learning outcomes are 53.85%, with high learning outcomes are 26.92%, and students with very high learning outcomes are 3.85%, with a completeness percentage of 65.38%. Low learning outcomes can be seen from interviews with students that 69.23% of students need help understanding the material the teacher explains during the learning process. In addition, from the results of interviews with subject teachers, it was obtained that aspects that often affect student learning outcomes are internal aspects, including lack of student interest in learning, lack of ability to understand the material, lack of student memory, lack of student skills in arithmetic and aspects of External factors include the lack of attention and support from the family to return to the lessons given by the teacher at home.